The Resurgence of Sea Piracy in Southeast Asia - Éric Frécon (Institut de recherche sur l'Asie du Sud-Est contemporaine, 2008)
Eric Frécon's study starkly reveals the fragility of the internal societies and the inadequate regulation of the Asian region by boldly plunging into a reality- that of piracy- that during the Cold War had been habitually restricted to notes of secret agents or for the reports of some original journalists. The study is an interesting approach. The development of terrorism has in fact confirmed it: a major part of the current scenario which matters now is that of the underground, economic, mafia-like or terrorist forces, forces that are beyond control and of which sometimes the nations are fully aware. Piracy is therefore an important phenomenon today; its analysis allows us to measure the power of the nations and the regulation of international zones. But the investigation is difficult and calls for intelligence, passion, the audacity to search in the dark and the courage to not be taken in: these are the very qualities that this work embodies. This book constitutes an excellent photograph of the weaknesses but also of the recovery of the Asians. It explains how piracy reappeared massively after the Cold War, firstly on account of the general deficiencies of the region and the weaknesses (or tactics) of some nations. But it also shows that the region has evolved. When I brought it up in 1998 in "L'Asie en danger", piracy was partially imputable to the internal situation and to the foreign policy of China. Since then, the collapse of Indonesia and the recovery of the Chinese regime have pushed it back towards the Straits of Southeast Asia. Eric Frécon's book also describes how the efforts of regional coordination and the policies of certain big nations like Japan and India acted upon piracy, in order to contain it, on the whole. The problem seems to have, since then, been identified and to a large extent handled; one may hope that it will be resolved in the years to come, even though the Indonesian crisis may seriously impede regulation efforts.